2014
DOI: 10.1038/mp.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic stress, oxidative stress and post-traumatic stress disorder: neurodegeneration and the accelerated-aging hypothesis

Abstract: Posttraumatic stress disorder (PTSD) is associated with elevated risk for a variety of age-related diseases and neurodegeneration. In this paper, we review evidence relevant to the hypothesis that chronic PTSD constitutes a form of persistent life stress that potentiates oxidative stress (OXS) and accelerates cellular aging. We provide an overview of empirical studies that have examined the effects of psychological stress on OXS, discuss the stress-perpetuating characteristics of PTSD, and then identify mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
171
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(195 citation statements)
references
References 128 publications
(115 reference statements)
5
171
0
1
Order By: Relevance
“…Persons with PTSD, compared to those exposed to trauma but did not develop PTSD, show alterations in inflammatory pathways, lipids and neuroendocrine dysfunction similar to individuals with prevalent cardiovascular disease and type-2 diabetes, and emerging evidence suggests PTSD may be related to accelerated aging [14,15]. However, few epidemiological studies have measured biomarker levels before and after PTSD onset.…”
Section: Two Open Questionsmentioning
confidence: 99%
“…Persons with PTSD, compared to those exposed to trauma but did not develop PTSD, show alterations in inflammatory pathways, lipids and neuroendocrine dysfunction similar to individuals with prevalent cardiovascular disease and type-2 diabetes, and emerging evidence suggests PTSD may be related to accelerated aging [14,15]. However, few epidemiological studies have measured biomarker levels before and after PTSD onset.…”
Section: Two Open Questionsmentioning
confidence: 99%
“…Papers by Miller and Sadeh [3] and Shaleh et al [4] detail a relationship between telomere erosion and stress-related depressive disorders. The nature of the relationship, if any, between, on the one hand, cortisol levels and depression and, on the other hand, telomere length and aging, is uncertain.…”
Section: Depression Cortisol Aging and Carnosinementioning
confidence: 99%
“…Another recent paper [2] has shown that major depressive disorder (MDD) is associated with reduced telomere length, increased susceptibility towards agerelated dysfunction and raised cortisol levels in response to stress, while two other recent papers have described an association between decreased leukocyte telomere length and stress-associated disorders [3,4]. It is objective of the present communication to suggest that (i) carnosine insufficiency could provide a link between stress and depression-associated phenomena and age-related dysfunction, and (ii) carnosine may possess therapeutic potential towards depression and stress-associated disorders when administered as a dietary supplement.…”
mentioning
confidence: 99%
“…We prioritize the role of PTSD, over and above that of trauma and stressor exposure, because we view its symptoms as part of a stress-perpetuating intraindividual environment that exerts effects on peripheral and central biological processes and ultimately contributes to disease, especially when symptoms are chronic (5). Protracted experiences of exaggerated startle, emotional and physiological reactivity to trauma cues, anger and arousal, and poor sleep may directly promote neuroimmune, autonomic, metabolic, HPA axis, oxidative stress, and other biological dysregulation (2,5).…”
mentioning
confidence: 99%
“…Protracted experiences of exaggerated startle, emotional and physiological reactivity to trauma cues, anger and arousal, and poor sleep may directly promote neuroimmune, autonomic, metabolic, HPA axis, oxidative stress, and other biological dysregulation (2,5). Over time, the cumulative burden of these symptoms and their associated physiological correlates may contribute to increased allostatic load, which broadly dysregulates homeostatic biological processes, thereby contributing to multiple types of medical morbidities (2,6).…”
mentioning
confidence: 99%